2004
DOI: 10.1111/j.0031-9317.2004.0284.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamics of non‐structural carbohydrates in bulbs and shoots of the geophyte Galanthus nivalis

Abstract: Seasonal dynamics of non-structural carbohydrates were studied in Galanthus nivalis L. over a 2-year period. The plants were collected in the field and separated into above- and below-ground biomass. The polysaccharide fraction of the bulbs consisted of fructans and starch. Seasonal variations suggest that the polysaccharides were utilized for carbon and energy supply for re-growth and flower development. With the re-sprouting of the bulbs in autumn the fructans within the bulbs were depolymerized and an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 45 publications
4
23
0
Order By: Relevance
“…The specific sink for the carbon assimilated by the Galanthus inflorescence cannot be exactly predicted from the data set collected, but the expanding basal leaves are expected to invest most of the assimilates both on their own growth and on filling the bulbs. During rapid shoot growth and fruiting, the bulbs and the above-ground organs were even assumed to be competing sinks for the photosynthetically fixed carbon, because refilling of carbohydrate reserves of the bulbs starts in February/ March (Orthen and Wehrmeyer, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The specific sink for the carbon assimilated by the Galanthus inflorescence cannot be exactly predicted from the data set collected, but the expanding basal leaves are expected to invest most of the assimilates both on their own growth and on filling the bulbs. During rapid shoot growth and fruiting, the bulbs and the above-ground organs were even assumed to be competing sinks for the photosynthetically fixed carbon, because refilling of carbohydrate reserves of the bulbs starts in February/ March (Orthen and Wehrmeyer, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Avila-Fernandez et al (2007) have found that in A. tequilana plants, the enzyme 1-SST showed an estimated kcat value of 260 min À1 , corresponding to a lower turnover number than the value of kcat observed for 1-SST from H. tuberosus (1566 min À1 ). This could explain why in A. tequilana plants the accumulation of sugars is slower with longer times for harvest (8-12 years) than other typical fructan producing plants ( AvilaFernandez et al, 2009;Cedeño, 1995;Monti et al, 2005;Orthen & Wehrmeyer, 2004;Saengthongpinit & Sajjaanantakul, 2005;Shiomi et al, 2005;Wilson et al, 2004). In Fig.…”
Section: Profile Of Water-soluble Carbohydrates Obtained By Hplc Hpamentioning
confidence: 93%
“…1, it can be inferred that at 2 years, the synthesis of fructans was beginning and the accumulation of fructans as reserve carbohydrate was in the initial phase. The increase of sugar accumulated as fructans has been observed also in physiological process of multiple plants, like the seeds maturation process of onion (Allium cepa L. ''W202"), during re-growth and flower development of Galanthus nivalis bulbs and during maturation process of Cichorium intybus L. and Helianthus tuberosus L. (Monti et al, 2005;Orthen & Wehrmeyer, 2004;Saengthongpinit & Sajjaanantakul, 2005;Shiomi et al, 2005;Wilson et al, 2004). The common characteristic of the accumulation processes in these plants is that normally the accumulated fructans are linear with b(2?1) linkages whereas in A. tequilana and other graminans like Urginea maritima they are highly branched (Spies et al, 1992).…”
Section: Profile Of Water-soluble Carbohydrates Obtained By Hplc Hpamentioning
confidence: 95%
See 2 more Smart Citations